2016
DOI: 10.1097/md.0000000000003959
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic resection or transarterial chemoembolization for hepatocellular carcinoma with portal vein tumor thrombus

Abstract: The role of hepatic resection in hepatocellular carcinoma (HCC) with accompanying portal vein tumor thrombus (PVTT) remains controversial. This study aimed to evaluate the surgical outcomes of hepatic resection compared with those of transarterial chemoembolization (TACE) in HCC patients. A retrospective study was conducted using the medical records of 230 HCC patients with portal vein invasion who underwent hepatic resection (96 patients) or TACE (134 patients). The baseline characteristics, tumor characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 28 publications
1
47
0
Order By: Relevance
“…The details and reasons for exclusion requiring consensus between the authors are described in http://onlinelibrary.wiley.com/doi/10.1002/hep.29883/suppinfo. Finally, 18 studies reporting PH versus TACE in BCLC stage B or stage C patients were included in the systematic review and meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The details and reasons for exclusion requiring consensus between the authors are described in http://onlinelibrary.wiley.com/doi/10.1002/hep.29883/suppinfo. Finally, 18 studies reporting PH versus TACE in BCLC stage B or stage C patients were included in the systematic review and meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen trials (one RCT, five PSM NRCTs, and 12 NRCTs) consisting of 20 data sets and a total of 5,986 patients were included in the meta‐analysis. The RCT was a single‐center trial conducted in China .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery has been considered contraindicated by many institutions, including the BCLC system [41] . However, many studies, particularly those from the Asian centers, have reported hepatic resection to be safe and effective for patients with portal vein invasion [28,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] [ Table 3]. The median 1-, 3-and 5-year overall survival rates for patients with all forms of portal vein invasion treated with surgery were 61.0%, 32.9% and 27.0% respectively.…”
Section: Surgerymentioning
confidence: 99%
“…[48] Vp1 to Vp3 181 60 42 33 32 2002-2012 2016 China Zheng et al . [49] All Choi et al . [76] Vp1 Table 10].…”
Section: -2012 2014mentioning
confidence: 99%